Critical thinking dispositions of new intake engineering technology students - Sarudin, Isarji; Mohamad All, Afiza; i Abdul Aziz, Muhammad Nadzr; Zubairi, Ainol Madziah (Universiti Malaysia Perlis, 2011)

(untitled)
Problem-solving and critical thinking abilities serve as important outcomes of any engineering programme. Engineering students are expected to solve problems, ask questions, research, and discover relevant information, and consider new ideas. This paper presents the findings a study to determine the initial critical thinking dispositions of new intake engineering technology students in the effort to provide base-line data for the integration of critical thinking (CT) in the English syllabus of the engineering technology programme. This is part of a larger English curriculum review exercise with a special focus on the integration of soft skills. A 10-item self-assessment questionnaire was distributed to 1425 new intake engineering students. When the findings of the CT dispositions are considered, CT dimension of detecting bias and exaggeration was cited the most among respondents. Low CT dimensions are evaluation and compare and contrast. Additional findings from focus group interviews reveal peculiar yet interesting insights on CT among the students. Implications of the findings in relation to CT for engineering technology students are discussed.